(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
This article is a continuation of the series of technique training in orthodontics especially for the postgradute trainees as well as for the practitioners who will learn and practice Fixed Appliance Technique. Once again, I believe that post-graduate trainee doctors, faculty members, private practitioners and all other concerned will find this article as a guide line during their training as well as in their professional practicing period. The article describes the technique training and design of standard edge-wise-technique in sequential stages with illustrated case reports for treating class III molar relationship with crowded arch in maxilla and anterior cross bite. The author acknowledges that the article is summarized from the lectures, handouts during his postgraduate studies in Kyushu University and Hiroshima University, Japan DOI: http://dx.doi.org/10.3329/bjodfo.v1i2.15989 Ban J Orthod & Dentofac Orthop, April 2011; Vol-1, No.2, 29-36